Effect of Nickel Supplementation on Growth Performance and Blood Metabolites of Growing Muzaffarnagari Lambs - A. Kumar; D.S. Sahu; G.Chandra; S.P. Yadav; D. Roy; A. Fahim; R.K. Singh; D.K. Yadav; P.S. Maurya (Indian Journal of Animal Nutrition, 2024)
The current study was designed to investigate the impact of nickel (Ni) supplementation on growth performance and blood metabolites of growing Muzaffernagari lambs. 18 growing lambs of age (10.33±0.67 months) and weight (30.45±3.67 kg) were utilized and randomly distributed into 3 groups, with 6 lambs in each. The offered basal diet was similar in all groups except for Ni supplementation which fed at rates of 0.0 (N0), 1.5 (N1.5), and 3.0 mg/kg DM (N3.0), respectively. Body weight (BW) and feed consumption (FC) were recorded at fortnightly intervals. The blood was sampled on 0, 15, 30, 45, 60, 75, and 90 d of the study period from the jugular vein in EDTA containing test tubes in the morning (07.30 h) before feeding and watering. BW and FC were not influenced by the supplementation of any dose of Ni and were reported statistically similar (P>0.05) in all the groups. The BW gain (BWG) was statistically (P